Migration and innovation: A survey - Sheida Rashidi; Andreas Pyka (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2013)
In a world characterized by competition on a global scale, persistent structural change driven by innovation and aging societies in industrialized economies, also the competition for the best talents on the labour markets becomes global and more intensive. Therefore it is not surprising that old-fashioned brain drain explanations for migration are no longer convincing. In the knowledge-based economies of the 21st centuries the ideas of brain circulation and international (diaspora) innovation networks become prevailing and should guide the design of migration policies. This paper is a survey on the theoretical and empirical approaches which address the important relationship between migration and innovation.
urn:nbn:de:bsz:100-opus-8820
Keywords: 330; Innovation; Migration